Evaluating and Implementing Strategies: Technogoly Based Financial Inclusion - Shaik, Gowsya; P. Raja Babu, Dr (International Journal of Engineering and Technology, 2018)
Now a day, Financial Inclusion is delivering the banking services to the people at an reasonable price to all the huge sections for low revenue group. For achieving social benefits and objectives and also to obtain a desired economic development, RBI puts continues efforts for fulfilling the financial inclusion programme. In this direction several new initiatives were undertaken by the Government of India and it has given approval on financial inclusion plans (FIPs) for sustainable development of an economy. These are including opening bank branches, Overdraft facility for eligible accounts, transaction in Kisan Credit Cards, General Credit Card Accounts and transactions through the BC-Information Communication Technology (ICT) channel. The main objective of this research paper to know the strategy based financial inclusion and to find out the implementation and achievement of financial inclusion in India during the period of 2012-17.Â